?INDOLE DERIVATIVES AS ANTIBACTE- RIAL AGENTS. STRUCTURE-ACTIVITY llELATIONSHIP (Biological Sciences - PJSIR, 2000)
In an effort to screen antibacterial activity of indole deriva- tives, various indoles containing diverse groups were prepared. The literature search has revealed that although many studies have been reported on other pharmacological aspects cut, to our knowledge, only one such reference exists where some indole derivatives (I) were noted to have exhib- ited antibacterial property (Archer and Schulenberg 1965).